Complete mitogenome of a Baltic Sea specimen of the non-indigenous polychaete Marenzelleria neglecta. Issue 1 (2nd January 2019) - Gastineau, Romain; Wawrzyniak-Wydrowska, Brygida; Lemieux, Claude; Turmel, Monique; Witkowski, Andrzej
Abstract: We sequenced the complete mitogenome of Marenzelleria neglecta, a non-indigenous polychaete of the Baltic Sea originating from North America. This is the first complete mitogenome made available for the family Spionidae. The genome is 15, 339 bp with a gene order identical to the generic order of the Pleistoannelida. The multigene maximum likelihood phylogeny, based on all protein-coding genes, weakly resolved the position of M. neglecta, as it tended to asssociate it with species representing the basal lineage of Annelids. This result underlines the need for more mitogenomes of Spionidae in order to improve the accuracy of their phylogeny.